Location of foreign direct investment in vertically related markets - Chrysovalantou Milliou (Center for Economic Studies and ifo Institute (CESifo), 2013)
We provide an alternative explanation for the commonly observed FDI in developed countries (DCs) considering a vertically related market structure and endogenizing vertical technology transfer (VTT). We show that even though VTT is more costly in a less developed country (LDC), a multinational does not always transfer less technology there than in a DC. Moreover, we show that a multinational sometimes locates its FDI in a DC where, although downstream competition is stronger than in a LDC, it can obtain the input at better terms due to VTT. Independently of whether the host country is more or less developed, FDI is always welfare-enhancing.
Keywords: L13; F12; F23; 330; foreign direct investment; host country; vertical relations; developed countries